Maternal Uterine Artery Doppler and Serum Marker in the First Trimester as Predictive Markers for Small for Gestational Age Neonates and Preeclampsia: A Pilot Study - Je Yeon Lee; Kyung A Lee; So Yun Park; Soo Jung Kim; So-Yeon Shim; Young Ju Kim; Mi Hye Park (Diagnostics)
Background/Objectives: Although preeclampsia (PE) and small for gestational age (SGA) are known to come from impaired placentation during the first trimester, prior studies have focused mostly on Doppler findings in the second trimester. Methods: In this retrospective pilot study, we enrolled 628 singleton pregnant women who underwent ultrasound in both the first and second trimesters and blood test. For SGA correlation, we further excluded 12 subjects with PE because PE may be the cause of SGA. We first presented the reference range of parameters of uterine artery Doppler in the first trimester and then grouped the subjects according to the presence of SGA (presence = 104, absence = 512) or PE (presence = 12, absence = 616) and investigated the association of uterine artery Doppler findings and serum markers in the first trimester with the occurrence of SGA or PE. Results: The uterine artery pulsatility index and the resistance index and the proportion of uterine artery notch decreased progressively in the first trimester. A lower serum beta-hCG level in the first trimester predicted the occurrence of SGA (adjusted odds ratio [AOR] = 0.53, p = 0.019), while the presence of the uterine artery notch in the first trimester predicted the development of PE (notch at least on one side: AOR = 8.65, p = 0.045 and notch on both sides: AOR = 8.91, p = 0.047). Regardless of whether a notch was present in the second trimester, a uterine artery notch in the first trimester was associated with an excellent negative predictive value (99.6%) for PE. Conclusions: This study suggests the clinical importance of assessing serum beta-hCG and the uterine artery notch in the first trimester to predict SGA and PE.